Monopolies and patents : a study of the history and future of the patent monopoly - Fox, Harold G. (Harold George), 1896-1970 (University of Toronto studies. Legal series. Extra volume., 1947)
Harold G. Fox is a native of Toronto and a graduate of the University of Toronto and the Law School of Osgoode Hall. For some years he practised patent and trade mark law as a member of the firm of Fetherstonhaugh & Fox. In the nineteen-twenties he was invited to take over the management of the Canadian zipper industry and, since that time, has devoted his main energies to the development of that business. But, while he is identified today as a competent industrial executive, he is also recognized as an authority in his special field of patent, trade mark, and copyright law, in which he has continued to take a deep interest. He believes that a lawyer makes a good businessman. He has, therefore, pursued not only the academic aspect of his profession but has kept an intimate contact with it both as counsel and as writer. He is the author of several standard text-books on Canadian law--Canadian Patent Law and Practice (1937), The Canadian Law of Trade Marks and Industrial Design (1940), and The Canadian Law of Copyright (1944). He is the editor of Fox's Patent, Trade Mark and Copyright Cases, now in its sixth volume, and is a considerable contributor to legal periodicals in this country and in the United States. He was appointed King's Counsel in 1937 and is a Fellow and some-time President of the Patent Institute of Canada. He holds the honorary appointment in the University of Toronto Lecturer in the Law of Industrial Property and, in 1945, in recognition of his contributions to Canadian legal scholarship, the University conferred on him the honorary degree of Doctor of Letters. Dr. Fox has decided views on the benefits which are conferred on the industrial and commercial life of a country, and, indeed, on the public generally, by a strong patent system efficiently administered. In his view, the modern patent of invention is not a monopoly, in the sense in which that word is generally understood. He feels that the modern witch-hunt against monopolies is misdirected when it levels its attack on the patent system and predicates the opinion that, if the history of monopolies were better understood, much of the antagonism against them would tend to disappear. It is an exponent of this view that he examines, in this work, the reasons for the institution and development of monopolies, the factors which contributed to their growth in England in the sixteenth and seventeenth century, and the cause of their gradual decline and transition into the modern patent of invention. The approach to the subject is not, however, merely antiquarian. In his opinion the patent system can be improved in the interests not only of the inventor but also of the public. With this thought in mind he proposes an amendment to the patent system designed to eliminate the indefinable element of inventive ingenuity from the content of patentability, a reform which would remove much of the uncertainty of result which in the past has been the main fault of the patent system and the chief curse of the inventor and patentee. In this work Dr. Fox demonstrates an attitude toward monopolies and patents which reflects both his legal training and research and his practical industrial experience. Whether one agrees with his interpretation of the history of monopolies and his proposal for amendment of the patent system or not, this book will evoke much interest and possible controversy.